SOIL LIQUEFACTION SUSCEPTIBILITY AND HAZARD MAPPING IN THE RESIDENTIAL AREA OF KüTAHYA (TURKEY) - Yilmaz I.; Bagci A. (My University, 2006)
This study presents the results of both field and laboratory tests that have been undertaken to assess liquefaction susceptibilities of the soils in Kütahya city, located in the well-known seismically active fault zone. Liquefaction potentials of the sub-surface materials at Kütahya city were estimated by using the geological aspect and geotechnical methods such as SPT method of field testing. And, the data obtained have been mapped according to susceptibility and hazard. The susceptibility map indicated “liquefable” and “marginally liquefable” areas in alluvium, and “non-liquefable” areas in Neogene unit for the magnitude of earthquake of M=6.5; whereas, liquefaction hazard map produced by using of liquefaction potential index showed the severity categories from “very low” to “high.” However, a large area in the study area is prone to liquefy according to liquefaction susceptibility map; the large parts of the liquefable horizon are mapped as “low” class of severity by the use of the liquefaction potential index. It can be said that hazard mapping of liquefaction for a given site is crucial than producing liquefaction susceptibility map for estimating the severity. Both the susceptibility and hazard maps should be produced and correlated with each other for planning in an engineering point of view.
Keywords: KüTAHYA; LIQUEFACTION; HAZARD; SEVERITY; STANDARD PENETRATION TEST; SUSCEPTIBILITY; Neogene; Cenozoic::Neogene; Кайнозой::Неоген